2021
DOI: 10.3389/fonc.2021.593561
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Molecular Features and Treatment Options for Small Bowel Adenocarcinoma

Abstract: Small bowel adenocarcinoma (SBA) is a rare malignancy characterized by poor prognosis. Recent efforts have sought to elucidate the genetic landscape and the molecular drivers behind this disease. Herein, we report the main molecular alterations in two metastatic (stage IV) SBA patients. Interestingly, one of them had gene alterations that affected signaling pathways previously described for SBA. However, a second patient displayed previously unreported alterations in this particular tumor type. Based on these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The use of chemotherapy as adjuvant treatment has been increasing [9] although the research around its use is still ongoing and not fully established due to the lack of randomized trials. The use of palliative chemotherapy in cases of advanced-stage unresectable SBA is the preferred standard treatment [11] and various retrospective studies have suggested prolonged overall survival (OS) rates with its use [4], although only a few protocols have been studied in literature and those regimens are based on protocols used for colon cancer. The FOLFOX regimen, using oxaliplatin-based chemotherapy seems to be the best choice, and its recommended by the French guidelines as 1st line therapy nowadays [12].…”
Section: Discussionmentioning
confidence: 99%
“…The use of chemotherapy as adjuvant treatment has been increasing [9] although the research around its use is still ongoing and not fully established due to the lack of randomized trials. The use of palliative chemotherapy in cases of advanced-stage unresectable SBA is the preferred standard treatment [11] and various retrospective studies have suggested prolonged overall survival (OS) rates with its use [4], although only a few protocols have been studied in literature and those regimens are based on protocols used for colon cancer. The FOLFOX regimen, using oxaliplatin-based chemotherapy seems to be the best choice, and its recommended by the French guidelines as 1st line therapy nowadays [12].…”
Section: Discussionmentioning
confidence: 99%
“…The two main histotypes of them are adenocarcinoma, covering around 30% to 40% of cases and neuroendocrine tumors accounting for 35-42%. Other gastrointestinal tumors -sarcomas, and lymphomas -consist of 20-25% of the small intestine cancers [2]. Small bowel adenocarcinoma (SBA) provides a rare problem including less than 3% of gastrointestinal tumors and about 0.5% of all malignant tumors.…”
Section: Introductionmentioning
confidence: 99%